2021
DOI: 10.3201/eid2709.204706
|View full text |Cite
|
Sign up to set email alerts
|

Ecologic Determinants of West Nile Virus Seroprevalence among Equids, Brazil

Abstract: W est Nile virus (WNV) is a widely distributed arthropodborne fl avivirus transmitted predominantly by Culex mosquitoes (1). Among infected persons, ≈20% show clinical signs, such as mild fever, rash, joint pain, headache, vomiting, and diarrhea (1,2); ≈0.7% have severe illness, such as encephalitis, meningitis, acute fl accid paralysis, respiratory failure, and even death (1). Beyond vectorborne transmission, transfusion-transmitted WNV infections have endangered blood safety (3). Equids are susceptible to WN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Due to the specific ecological interactions between bird and vector populations, bird protection areas have been highlighted as a potential risk factor for infection [75][76][77][78]. As the entire study area here was located in the same temperate climatic zone, the observed differences likely cannot be explained by the prevailing climatic conditions, of which temperature and precipitation have been identified as the most critical factors influencing the spread of WNV [77,79,80]. However, variations in temperature-dependent extrinsic incubation times (EIP) have been estimated within the study area [54,80].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the specific ecological interactions between bird and vector populations, bird protection areas have been highlighted as a potential risk factor for infection [75][76][77][78]. As the entire study area here was located in the same temperate climatic zone, the observed differences likely cannot be explained by the prevailing climatic conditions, of which temperature and precipitation have been identified as the most critical factors influencing the spread of WNV [77,79,80]. However, variations in temperature-dependent extrinsic incubation times (EIP) have been estimated within the study area [54,80].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, experimental infection and serological evidence indicate circulation of West Nile virus (WNV) and Japanese Encephalitis virus (JEV) in cats and dogs [12–15] and of Wesselsbron virus (WSLV) in cattle, goat and sheep [15–21]. Virus detection by molecular methods, virus isolation and serological evidence substantiate that horses can be infected with WNV, Saint Louis Encephalitis virus (SLEV), JEV and Usutu virus (USV) [22, 23]. Livestock species, such as sheep and goats, were susceptible to ZIKV in vivo [24, 25], and although ZIKV-specific neutralizing antibodies were reported in sero-epidemiological studies in cattle and sheep from Brazil and in horses from French Pacific Islands [26, 27], only few flaviviruses beyond ZIKV were used in those studies to rule out potentially unspecific test results elicited by cross-reactive flavivirus antibodies.…”
Section: Full-textmentioning
confidence: 99%
“…However, the sample size of USUV positive sera in general and USUV IgM positive sera in particular used in this study was limited due to the low number of diagnosed human cases and a further validation of the assay would be necessary with a higher sample quantity. Given the importance of epidemiological surveillance of WNV and USUV in susceptible vertebrates, further studies should investigate the potential of the Equad protein‐based ELISAs also with veterinary samples such as sera derived from birds like it has previously been shown for horses and mules (Oliveira‐Filho et al., 2021; Rockstroh et al., 2019).…”
Section: Discussionmentioning
confidence: 99%